Dinámica sistémica de la norma ISO 9002: 1994 - Jiménez Rojas, Álvaro Hernán; Campos Sosa, Carlos Fernando; Correcha Ramírez, Flor Yaned (Ingeniería, 1999)
The structure and development of quality system which is based in ISO 9000 standard has to be implemented with the systems focus of the standard, not only with the components of this, but also with the organization of its correlations. The systemic focusing can be defined as a conceptual methodology where the participants are involved in a process and on this way they can translate the general items of the standard into particular items that can be focused on the organization.That systemic focus was applied in an important transnational services company and this work was useful for the results that wild be obtain with the interpretation and analysis by the workers of the organization. More over, it contributes toapply a better concept of the changes in ISO 9000: 94 standard to make defined targets to the ISO 9000:2000 standard.